Psicologia educacional e escolar: inspirando ideias para a formação continuada de educadores por meio da arte - Pessoa, Camila Turati (2014)
In this dissertation we aimed at understanding how Educational and School Psychology, together with Art, could contribute to the continuing formation of educators. We know that working in education demands disposition all the time/at any time to share and think together about practices that can encompass professionals working on those contexts. In addition to performing actions in schools daily routines, it is necessary to think of theoretical framework that helps to underpin those actions, in order to effectively integrate them into educational activities. Taking into consideration this articulation between theory and practice and offering spaces for educators to share and study about issues involving their jobs, we offer a proposal of continuing education, in groups, wishing to contribute to the development of the educator in cognitive, affective, social and aesthetic aspects. We chose art as our main object in this work , because we consider it to instigate the development of higher mental functions due to its different languages and also because it broadens the cultural repertoire of subjects, in addition to working expressiveness, creativity and other aspects which are essential to the teaching function. Moreover, in order that the professional can propose different activities within the classroom, which stimulate the student s learning processes and take into consideration the particularities of each person, it is necessary that the teacher experience it too, take ownership of it and thus he will be able to share those experiences with other people. Thus, we proposed ten meetings, with four hours each, at a formation center located in the Municipality of Uberlândia Minas Gerais, with voluntary participation of municipal teachers. We joined together during a semester and each meeting was organized in a format that primarily involved a theoretical part and later a practical part with a moment dedicated to share experiences. The meetings themes involved visual arts, literature, music, theater, movies, and also included theoretical and conceptual formation aspects of the participants, especially the cultural-historical approach and continuing training/formation of teachers/educators. In all meetings we proposed activities that sought to contribute to educators personal and professional development and to provide tools to think and rethink their activity in educational contexts. The proposal was analyzed by means of records made by the participants in their logbooks, in the Group s Notebook and by observation and participation of the researcher during the course. After a close reading of the material, we selected three main guiding points of analysis, which were aggregated by similarity with respect to their content, as follows : a) Educators in extension course: trajectories and reflections, b) Art as a differentiated formation possibility and c) Reflections on the role of educational and school psychologists in formation contexts. So forth, we have established some dialogues based on those records, thinking of dialogues between education, Art and Psychology as well as its contributions to the continuing formation of educators. We would like to highlight the importance of the educational and school psychologist inserted in these contexts, and we especially used Art as a distinguished element of formation, constructing works which aim at helping both Psychology and Educational areas.